2015
DOI: 10.1016/j.cbpra.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Using Measurement-Based Care to Enhance Any Treatment

Abstract: Measurement-based care (MBC) can be defined as the practice of basing clinical care on client data collected throughout treatment. MBC is considered a core component of numerous evidence-based practices (e.g., Beck & Beck, 2011; Klerman, Weissman, Rounsaville, & Chevron, 1984) and has emerging empirical support as an evidence-based framework that can be added to any treatment (Lambert et al., 2003, Trivedi et al., 2007). The observed benefits of MBC are numerous. MBC provides insight into treatment progress, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
303
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 384 publications
(305 citation statements)
references
References 85 publications
2
303
0
Order By: Relevance
“…MBC is defined as the use of data collected throughout treatment to drive clinical decisions (Scott & Lewis, 2015), and is often used interchangeably with related terms such as routine outcome monitoring or patient-reported outcome monitoring (Bickman et al, 2016; Lyon, Lewis, Boyd, Hendrix, & Liu, 2016). A substantial body of evidence supports the utility of MBC and systematic assessment in enhancing both intervention processes (e.g., improved patient-clinician relationships, client-centered services, engagement in services) and outcomes for adult and youth service recipients (Bickman, Kelley, Breda, de Andrade, & Riemer, 2011; Carlier et al, 2012; Cashel, 2002; Douglas et al, 2015; Jewell, Handwerk, Almquist, & Lucas, 2004; Rettew, Lynch, Achenbach, Dumenci, & Ivanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBC is defined as the use of data collected throughout treatment to drive clinical decisions (Scott & Lewis, 2015), and is often used interchangeably with related terms such as routine outcome monitoring or patient-reported outcome monitoring (Bickman et al, 2016; Lyon, Lewis, Boyd, Hendrix, & Liu, 2016). A substantial body of evidence supports the utility of MBC and systematic assessment in enhancing both intervention processes (e.g., improved patient-clinician relationships, client-centered services, engagement in services) and outcomes for adult and youth service recipients (Bickman, Kelley, Breda, de Andrade, & Riemer, 2011; Carlier et al, 2012; Cashel, 2002; Douglas et al, 2015; Jewell, Handwerk, Almquist, & Lucas, 2004; Rettew, Lynch, Achenbach, Dumenci, & Ivanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review of MBC with adults has questioned its impact on mental health symptoms, especially for clients other than those who are not-on-track (i.e., deteriorating or at risk for dropout) (Kendrick et al, 2016). Although its effects may be more attenuated than previously believed – at least among adults – the relative simplicity, low burden on clinicians, and existing evidence for effectiveness has led MBC to be identified as a minimal intervention necessary for change (Glasgow et al, 2013; Scott & Lewis, 2015). Unfortunately, research has consistently demonstrated that mental health cliniciansinfrequently engaged in MBC practices (e.g., regular administration of standardized assessment tools; data-driven decision making) (Gilbody, House, & Sheldon, 2002; Hatfield & Ogles, 2004; Lyon et al, 2015; Palmiter, 2004)and that factors such as clinician attitudes and previous training experiences may predict use (Connors, Arora, Curtis, & Stephan, 2015; Jensen-Doss & Hawley, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A key issue was deciding what items should be on the progress monitoring measure. As Scott and Lewis (2015) have noted, an important consideration is determining whether the items should be idiographic (i.e., tailored to the patient's specific problem) or nomothetic (i.e., standardized self-report measures that can be administered consistently over time). Based upon our initial experience and in consultation with the third party vendor, we decided to use a nomothetic approach which would simplify administration (same measure for each patient at each visit) and we used items that the vendor had identified were sensitive to change in a wide variety of clinical conditions (i.e., global distress) and were also psychometrically valid.…”
Section: Pilot Programmentioning
confidence: 99%
“…By routinely collecting standardized measures of depression severity, MBC helps providers identify response to treatment earlier than clinical judgment alone (Hatfield, McCullough, Frantz, & Krieger, 2010), yielding larger, faster, and less costly improvements in mental health symptoms (Hawkins, Lambert, Vermeersch, Slade, & Tuttle, 2004; Knaup, Koester, Schoefer, Becker, & Puschner, 2009). MBC may also foster better patient-provider communication and help patients and providers navigate treatment goals and shared decision-making (Scott & Lewis, 2016). Many practice organizations have called for systematic implementation of MBC, including the Institute of Medicine (IOM, 2006) and the American Psychiatric Association (Gelenberg et al, 2010).…”
Section: Measurement-based Carementioning
confidence: 99%